Perancangan Basisdata "Online Shop Buku Dokter" Dengan Menggunakan My SQL - Safar Dwi Kurniawan; Thomas Kristian Jeriko; Yohanes Edwin W (Media Aplikom, 2017)
This study aims to create a database on the sale of goods on the Online Shop Book doctor who housed Jl. Salemba Tengah II No.10, RT.5 / RW.8, Paseban, Senen, Central Jakarta. Creation of this database is useful to produce information fast, precise, accurate and relevant in live penjulan transaction on Online Shop Book Doctor. In this study before the database was designed using ERD as a conceptual form, continued the normalization process to eliminate the existence of multiple attributes on the entities, redundancies and anomalies that may occur in the database. Making Database Online Shop This Doctor Book uses MySQL as a DBMS in managing the information in the database. The researcher only makes recording of transaction penjulan on Online Shop Book Doctor with output transaction report and delivery of goods in the absence of financial statement, so this design as saranan owner of Online Shop Book Doctor in monitoring transaction on sale and delivery transaction. Keyword : Online Shop, Basis Data, My SQL